Studi Pengaruh Perbedaan Media Simpan Entres terhadap Keberhasilan Grafting Wani Ngumpen Bali (Mangifera caesia Jack. Var. Ngumpen Bali) - NYOMAN WISNU RAHADI; NI LUH MADE PRADNYAWATHI; NI NYOMAN ARI MAYADEWI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2022)
Study of Differences in Entres Saving Media on the Success of Grafting Wani Ngumpen Bali (Mangifera caesia Jack.Var. Ngumpen Bali) Wani (Mangifera caesia Jack.) is a local fruit plant that has a fairly high diversity of 22 cultivars in all wani production centers in Bali. One of the cultivars, namely Wani Ngumpen Bali, has the advantage of producing fruit that does not contain seeds as much as 90% of the total fruit. Due to constraints in generative seed production, wani are propagated vegetatively by means of grafting. Due to the limited time and the number of grafted seedlings, efforts are needed to maintain the freshness of the shoots through storage. The purpose of this study was to determine the best entres storage media for female grafting. This experiment used a Randomized Block Design (RAK), with five treatments, namely no media, sawdust, wet newspaper, wet cloth, and banana fronds. Each treatment was repeated five times and each unit consisted of three plants so that there were 75 experimental units. The data obtained were analyzed descriptively. The treatment of various storage media gave different responses to the success rate of grafting of Wani Ngumpen Bali plants. The best media for storing buds was wet newsprint with a success rate of 26.6% of live seedlings, supported by the number of leaves as many as 15 parameters.